Právo Evropské unie - Tomášek, Michal; Týč, Vladimír; Petrlík, David; Malenovský, Jiří; Pelikánová, Irena; Rozehnalová, Naděžda; Křepelka, Filip; Pítrová, Lenka; Sehnálek, David; Šmejkal, Václav; Exner, Jan; Kunertová, Tereza; et al. (Leges, 2021)
Vysokoškolská učebnice, která se zabývá právem Evropské unie.
Student
Keywords: právní vědy; Evropa; Jurisprudence; Europe; European Union; Evropská unie; právo, zákonodárství